(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2024)
In the context of the resurgence of the novel as a genre in 18th century Spain, after its near disappearance since the mid-17th century and through its gradual reintroduction into the national scene with translations of foreign works, the novel Luisa o La cabaña en el valle stands out. Written by the English translator, essayist and novelist Elizabeth Helme, and published for the first time in Spanish in 1797 by the publisher Francisco de Tójar, its case is striking for how soon it was translated and published in Spain, as well as for the success it enjoyed for almost half a century and for being a paradigmatic case of the novel by a female author and pedagogical intention that the Spanish Enlightenment approved. In spite of all this, it has not received significant attention from subsequent critics. By tracing editions of the work and studying various preserved textual documents, this paper analyzes the causes and interests that motivated the arrival of this work to Spain, as well as the way in which the novel frames itself in the ideological and social debates of the time. The study corroborates the powerful impact of the novel in its historical context.